Radiofrequency ablation in patients with left ventricular dysfunction induced by ventricular premature beats - B. Kravchuk; R. Maliarchuk; O. Paratsii (Ukrainian Journal of Cardiovascular Surgery, 2016)
Aim of study: evaluation of left ventricular systolic function and its dependence on the number of VPB in patients with VPB-induced left ventricular dysfunction, which was treated by radiofrequency catheter ablation (RCA).In the analysis included 11 consecutive cases of patients with RCA of monomorphic VPB and LV dysfunction. The age of patients ranged from 18 to 46 years, including 7 (63%) women. The criterion of LV dysfunction was reduced LV ejection fraction (LVEF) below 50%. In all patients RCA of VPB’s substrate was performed by the standard method. The criterion for the efficiency of procedures was the number of VPB <1% of the daily rhythm. Echocardiography was performed before the procedure and after 3 and 6 months; the daily monitoring of ECG was performed before the procedure, after 48 hours and after 6 months.RCA applications were performed in septal area of right ventricular outflow tract (RVOT) in 6 (54.5%) cases; RVOT free wall – in 3 (27.3%) patients and in 2 observations (18.2%) – in sinuses of Valsalva (p<0.05). In one case in RVOT was early recurrence of VPB and RCA, which was effective, repeated after 1 week. All patients experienced a significant reduction in the number of VPB after ablation and after 48 hours and 6 months (p<0,05). The number of VPB decreased from 34,415±6556,36 per day before ablation to 627,36±319,48 per day – 48 hours after ablation and 608,63±299,03 per day in 6 months after ablation. Percentage of VPB in the daily rhythm decreased from 33,62±6,06 before ablation to 0,6±0,32 48 hours after ablation and to 0,57±0,3 – 6 months after ablation, i.e. by 98%. LVEF increased from 43,82±3,19 before ablation to 54,27±4,47 after 6 months (p<0,05). Directly proportional relationship between the percentage of VPB in the daily rhythm and LVEF (p<0,05) was noted.In patients with VPB-induced LV dysfunction LVEF is in direct ratio to the percentage of VPB in a daily rhythm. RCA is effective method of treatment of VPB in patients with VPB-induced LV dysfunction, which enabled to reduce daily amount of VPB on 98% in the late period with reversion of LV dysfunction.